2011
DOI: 10.1007/s00167-011-1674-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after repair of recurrent post-traumatic anterior shoulder instability: comparison of arthroscopic transglenoid suture and open Bankart reconstruction

Abstract: Therapeutic Study-Retrospective Comparative Study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 33 publications
2
35
0
8
Order By: Relevance
“…Functional follow-up scores confirmed the good long-term results already reported in the literature after the same procedure [3-6,26,27,34]. Although patients with subscapularis muscle histopathologic anomalies had more recurrence in this study, their functional scores at follow-up were not significantly different when compared to patients with normal muscle histology.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Functional follow-up scores confirmed the good long-term results already reported in the literature after the same procedure [3-6,26,27,34]. Although patients with subscapularis muscle histopathologic anomalies had more recurrence in this study, their functional scores at follow-up were not significantly different when compared to patients with normal muscle histology.…”
Section: Discussionsupporting
confidence: 87%
“…The Constant-Murley shoulder score is not validated for patients undergoing surgery for shoulder instability [20]. We used this score at follow-up because it was already obtained preoperatively and it is reported in other long-term follow-up studies on open anterior shoulder stabilization, thus allowing for comparison [3,26,27]. The Rowe shoulder score, the ASES shoulder assessment and the SANE rating have been validated for the evaluation of patients after shoulder stabilization [25,28,29].…”
Section: Methodsmentioning
confidence: 99%
“…A prospective study reported up to 90% recurrence rate in young athletes under 24-year-old following a first time shoulder dislocation [47] . Specifically, participation in contact sports was a significant patient factor in developing recurrent instability [48,49] . It is important to identify the chronicity of the shoulder problem, the functional restriction and quantification of the glenoid and humeral bone loss prior to treatment.…”
Section: Managementmentioning
confidence: 99%
“…The longer the follow-up is, the higher redislocation rates are; this was stated by Zaffagnini et al ,44 who found, in a retrospective series with a follow-up from 10 to 17 years, a redislocation rate of 12.5% in 49 shoulders, and Plath et al ,45 who presented a case series with a 10-year follow-up, with a 21% redislocation rate in 100 shoulders. We could not stratify the recurrence risk for follow-up duration; however, a graphic representation of recurrence ratios plotted for average follow-up duration (figures 3–6) seems to confirm this statement.…”
Section: Discussionmentioning
confidence: 88%